Pengaruh Imbangan Silase Rumput Kume (Sorghum plumosum var timorense) dan Alysicarpus vaginalis yang Berbeda Terhadap pH, Konsentrasi NH3 dan VFA Residu Fermentasi In Vitro - Usboko, Maria Yunita G.; Enawati, Luh Sri; Maranatha, Grace (Animal Agricultura, 2024)
This study aims to determine the quality of forage silage of Sorghum plumosum var Timorense (Grass kume) and Alysicarpus vaginalis (Leguminosa). using a completely randomized design with 4 treatments and 4 repilications. The four treatments were AV0 (100% Kume grass), AV20 (80% Kume grass + 20% Alysicarpus vaginalis) AV40 (60% Kume grass + 40% Alysicarpus vaginalis), AV60 (40% Kume grass + 60% Alysicarpus vaginalis). The results obtained are the average. pH AV0: 6.450±0.24; AV20: 6.450±0.27; AV40: 6.500±0.25; AV60: 6.500±0.18. NH3 (mM) AV0:139.543 ±;13.30 AV20: 138.641±15.17 ;AV40: 146.169±15.74 14.365±2.30; AV60:  136.815±21.47. VFA (mM) AV0: 13.356±1.05; AV20: 13.814±3.28; AV40: 14.365±2.30 ; AV60: 13.473±1.16. The results of the analysis of variance showed that the treatment had no significant effect (P>0.05) on the Ph value, NH3 concentration and VFA so it can be concluded that kume grass and Alysicapus vaginalis silage had the same effect on pH, NH3 concentration, and VFA.